Predictive biomarkers along gastric cancer pathogenetic pathways. Issue 5 (4th May 2017) - Panarese, Iacopo; De Vita, Ferdinando; Ronchi, Andrea; Romano, Marco; Alfano, Roberto; Di Martino, Natale; Zito Marino, Federica; Ferraraccio, Francesca; Franco, Renato
ABSTRACT: Introduction : Gastric cancer is the second leading cause of cancer all over the world. Unfortunately, several gastric cancers are diagnosed in an advanced stage and chemotherapy and/or target therapies remain the only options to treat patients. Areas covered : Herein we evaluate the new molecular proposal of gastric cancer classification, offering the possibility to recognize different pathogenetic mechanisms and molecular biomarkers potentially useful for target therapies. Expert commentary : The possibility of introducing new specific tests for identification of molecular biomarkers critical for targeted therapies response represents the new frontier in the selection of gastric cancer patients to improve their survival. Besides HER2, already used in clinical settings as a target biomarker for biological therapy in gastric cancer patients with tissue cancer cells overexpressing HER2, other promising target biomarkers which are deregulated in gastric cancer, such as MET and FGFR, could be identified in tissue and then used for therapeutic purposes. In addition immunotherapy represents the most promising possibility of advanced gastric cancer treatment. In particular, as in other solid tumors, PD-1/PDL1 pathway has emerged in several clinical trials as an interesting therapeutic target.